BUILDING QUALITY EDUCATION IN PESANTREN THROUGH STRENGTHENING HUMAN RESOURCES PERFORMANCE - Rifa'i, Moh; Kholilullah, Kholilullah (Managere: Indonesian Journal of Educational Management, 2022)
This study aims to analyze the performance of human resources in improving the quality of education in Islamic boarding schools. This study uses a qualitative approach to the type of case study. Data collection techniques are carried out through interviews, observation, and documentation. The data analysis procedure was carried out interactively, starting with data collection, presentation, reduction, and concluding. The results of the study show that the performance of human resources in improving the quality of education in Islamic boarding schools is carried out through the competence of administrators in various fields, high aspirations, and support from leaders. This research provides implications about the importance of effective performance in realizing organizational goals.